Analytical Studies on Jarajanya Vishada (Geriatric Depression) in Light of Charaka Samhita and its Management with Ashwagandha Root (International Journal of Ayurveda and Pharma Research, 2023)
The state of Vishada (depression) which is seen during Jeernavastha (old age) can be termed as ‘Jarajanya Vishada’ in accordance with geriatric depression which is now days considered as world-wide phenomenon. Vata Dosha which becomes dominant during old age is also responsible for causation of Vishada. Geriatric depression is generally associated with higher medical morbidity and mortality, greater disability along with more neuro-psychological and neuro-radiological abnormalities which is also seen during Jeernavastha. Aims and Objectives: To evaluate the concept of Jarajanya Vishada in line of geriatric depression along with to evaluate the efficacy of the stipulated drug i.e., root of Ashwagandha (Withania somnifera Linn.) to combat the same. Materials and Methods: In selected 24 subjects of Jarajanya Vishada (geriatric depression) having inclusion and exclusion criteria based on Geriatric Depression Scale (GDS), selected therapeutic regimen (1. Shirodhara by warm decoction of root of Ashwagandha + 2. Avapida Nasya by fresh juice of Ashwagandha root along with 3. Oral intake of fresh juice of root of Ashwagandha) was administered for 30 consecutive days. Results: The result of the study revealed that, the stipulated therapeutic regimen with Ashwagandha has moderate efficacy (25% - 50%) on maximum cases of mild depression and mild efficacy (